ANALISIS STILISTIKA PADA PUISI “MAKAN MALAM DI RESTORAN BARU TIDAK JAUH PANTAI LOSARI” KARYA AAN MANSYUR - Tisya Rexa Oktavia; Mita Marisa Nirditaranti; Firnanda Putria Ananta; Wawan Hermawan (CV. Denasya Smart Publisher, 2025)
This study is motivated by the importance of stylistic analysis in understanding the use of language in poetry. This study focuses on idioms and figures of speech, but also analyzes general stylistics, including diction, imagery, and figures of speech in Aan Mansyur’s poem entitled “Makan Malam di Restoran Baru Tak Jauh dari Pantai Losari” (Dinner at a New Restaurant Not Far from Losari Beach). The purpose of this study is to explain how the use of idioms and figures of speech can enhance the poetic meaning, imagination, and atmosphere created by the poet. This study uses a qualitative descriptive method through in-depth reading, identifying stylistic elements, and interpretation based on Al-Ma’ruf’s theory. This study shows that the use of language styles such as personification, metaphor, and idioms is very important in bringing objects such as the moon, the sea, and the city to life, so that these objects become symbols of the characters’ feelings in the lyrics. Idioms such as “the rising tide,” “the bones of the city,” and “the scent of ordinary people’s work” reinforce the inner images, social criticism, and authenticity that the poet builds. In addition, the poet’s use of repetition and word choice enriches the composition of the poem and gives it a deep emotional rhythm. The conclusion of this study confirms that the combination of idioms and figures of speech can create dense poetic meaning and reinforce the message about humanity and the feelings that the poet wants to convey.